The orbital stability of a test body motion in the field of two massive bodies - Abishev Medeu (EPJ Web of Conferences, 2018)
We investigate the orbital stability of a test particle motion in the restricted three-body problem where all bodies have their own rotation. We have shown that it is possible to get some insight into the stability properties of the motion of test particles in restricted three-body problem, without knowing the exact solutions of the relativistic motion equations.